A study on students' difficulties in conducting research / Alif Akram Mohammad, Harry Ajang & Jeriemy Christopher Cheri - Mohammad, Alif Akram; Ajang, Harry; Cheri, Jeriemy Christopher
Our study was mainly created for students who majority taking Research Methodology as their main subject. Research Methodology as in Diploma in Public Administration is called Research Methodology and its code is PAD340. Meanwhile for Bachelor in Administration Science, the codes for research paper are dividing into two into code. The first one is ADS 501 which is for Proposal and another is ADS 554 which is for the Research paper. This subject is important as it is a main subject for Diploma in Public Administration and Bachelor in Administration Science students. It is compulsory to do the research in order for the students to graduate. Students are asked to form into a group which can consist from 2 to 4 in a group. Then, they must select among the lecturer in their own faculty to be their supervisor. The supervisor will give guidance to students and assist them in conducting their research. Since this subject is not an option for student to choose, they have to deal with many problems in conducting their research. That is why our study is focusing on student’s problem in conducting their research. Below here is a list of our problem statement regarding student’s problem in conducting their research.